Оптоэлектронные сенсоры газов на основе многоэлементных источников ИК-излучения - Kabatsiy, V. N. (PE "Politekhperiodika", Book and Journal Publishers, 2010)
The constructions of optoelectronic sensors to methane and carbon dioxide, taking into account the peculiarities of spectral characteristics of sources and receivers of medium IR-diapason spectrum are proposed. The possibility of use of optoelectronic sensors for the measuring of CH4 and CO2 concentration in diapason 0–3 vol.% is demonstrated.